Conservation of Energy and Momentum of Quasi Particles - Chanana, Ravi Kumar (European Journal of Applied Sciences, 2025)
The author through this brief communication wishes to publicize his findings of a differential form of conservation of energy and momentum of quasi particles. The contents of the paper are a repeat with some new thoughts and an application in the theory of the expanding Universe.